Oral verruciform xanthoma: The great imitator - Sweety Lalawat; Nalini Tomar; Arati Chaudhary; Vanaja Reddy (Wolters Kluwer Medknow Publications, 2020)
Oral Verruciform xanthoma (OVX) is an uncommon benign muco-cutaneous lesion having various concepts regarding its etiopathogenesis. Intraorally, this usually occurs on the gingiva and alveolar mucosa. Often asymptomatic, this lesion presents with a flat to verruco-papillary surface morphology. The clinical features of OVX can be misleading and resembles diverse hyperplastic, non-malignant, potentially malignant, and malignant lesions of the oral cavity. Histopathological examination is a key for the diagnosis of this lesion with xanthoma cells being the hallmark. Surgical excision remains the treatment modality and recurrence is rare. This paper presents a case of oral verruciform xanthoma on the buccal mucosa, mimicking a potentially malignant lesion, and a review of its major clinical, histological features and differential diagnosis.